Purification of priest, prophet and people : a comparative study of Zechariah 3 and 13 - O'Kennedy, Daniël Francois (Old Testament essays, 2014)
The book of Zechariah articulates different theological themes or perspectives. One of these themes is the purification or cleansing of the priest, prophet and people of Jerusalem. This article will compare two prominent chapters in Zechariah, paying particular attention to the theme of purification. The question posed by this article is: what are the differences and similarities between Zech 3 and 13? There are several differences between these two chapters. Chapter 3 forms part of the eight night visions and focuses more on the purification of Joshua, the high priest (3:1). Chapter 13 is part of the second oracle in Deutero-Zechariah and focuses more on the purification of the "house of David" and the people of Jerusalem (13:1). Different Hebrew words are even used to describe the sin and impurity of the people. In Zech 3 YHWH replaces the filthy clothes with a clean turban, but in Zech 13 the unclean spirit and prophets will be removed from the land. Despite all the differences, both chapters use the expression "on that day" (3:10; 13:1-2) and emphasise that the leaders have a significant responsibility. YHWH cannot purify Jerusalem (3:2; 13:1), the land (3:9; 13:2) and the people with unclean leaders (priests, prophets and shepherds). Both chapters close on a positive note, describing the effect of purification: there will be peace amongst the people (3:10) and the acknowledgement that YHWH is their God (13:9).